Temperate Soils Exposed to Drought—Key Processes, Impacts, Indicators, and Unknowns - Sabine Reinsch; David A. Robinson; Maud A. J. van Soest; Aidan M. Keith; Simon Parry; Andrew M. Tye (Land)
The summer drought in the United Kingdom (UK) in 2022 produced significant speculation concerning how its termination may impact and interact with the soil resource. Whilst knowledge regarding soils and droughts exists in the scientific literature, a coherent understanding of the wider range of impacts on soil properties and functions has not been compiled for temperate soils. Here, we draw together knowledge from studies in the UK and other temperate countries to understand how soils respond to drought, and importantly what and where our knowledge gaps are. First, we define the different types of droughts and their frequency in the UK and provide a brief overview on the likely societal impacts that droughts place on the soil and related ecosystems. Our focus is on ‘agricultural and ecosystem drought’, as this is when soils experience dry periods affecting crops and ecosystem function, followed by rewetting. The behaviour of moisture in soils and the key processes that contribute to its storage and transport are examined. The principal changes in the physical, chemical, and biological properties of soils resulting from drought, and rewetting (i.e., drought termination) are discussed and their extensive interactions are demonstrated. Processes that are involved in the rewetting of soils are explored for soil and catchment-scale soil responses. Lastly, soils’ recovery after drought is considered, knowledge gaps are identified, and areas to improve understanding are highlighted.